Sudan - Public Expenditure Tracking Survey (PETS) : Case Study of the Health Sector - World Bank (Washington, DC, 2013)
The Sudan referendum on post-Comprehensive Peace Agreement (CPA) arrangements was held during January 9-15, 2011 with results in favor of secession of the South by July 9, 2011. The economic effects will transmit largely through the fiscal and external accounts and the outcome of secession negotiations will determine the post-CPA economic landscape. The secession outcome will likely put significant strain on economic stability in the North. The PETS study is organized as follows: chapter two presents the objectives of the study, and the survey methodology and sampling size. Chapter three focuses on the specific developments of budget data (functional classification) in the Northern States. The chapter sheds some light on revenues and expenditure in Northern States and also zooms into the specific responsibilities transferred to the states. Towards the end, the chapter addresses the budgets specifically of the six states that have been sampled for the study (in a purposive sample). Chapter four is the heart of the study and is based on the flow of funds analysis underlying the PET survey. It starts out with addressing the question on 'who' finances the health sector. With this it gives a good account of the decentralized nature of health services, which is a prerequisite to actually track public spending through the system. Chapter five explores the interconnections between public expenditure and service delivery in Sudan and tries to assess the effectiveness of public spending in contributing to the quality of health services. Chapter six concludes with a highlight of the findings and possible policy options. Annex one provides six short extracts of the main findings and conclusions for each state as additional case studies.